Are Suicide Note Writers Representative of All Suicides? Analysis of the National Violent Death Reporting System. Issue 1 (16th December 2016) - Stack, Steven; Rockett, Ian R. H.
Abstract : While suicide notes can offer insights into the causes of suicide and clues for prevention, there is disagreement regarding the degree to which note leavers are representative of the general population of suicides. Previous relevant research on the United States is marked by a series of limitations: small local samples, an over focus on demographic constructs, and lack of multivariable analysis. This study uses a large national sample, a wide range of predictor variables, and multivariable statistical techniques to estimate more reliable similarities and differences between note leavers and other suicides. All data are taken from the National Violent Death Reporting System, which covers 17 states. A total of 9, 048 note writers were compared to 21, 522 other suicides in terms of 39 variables. In both bivariable (32/39 variables) and multivariable analyses (30/39 variables), note leavers differed from other suicides in most demographic variables, stressful life events, psychiatric issues, and methods of suicide. The national evidence suggests that caution be exercised in generalizing patterns found among writers of suicide notes to suicides in general. This is the first analysis of suicide notes using US data on the issue.